Consumers’ Awareness About Electricity Shortfall and Initiatives Taken by MSEDCL for DSM - Laddha, Seema (Prabandhan: Indian Journal of Management, 2015)
Continuous electricity at an affordable rate is most important for the socioeconomic development of a country. However, since the last few decades, there has been an alarming increase in the demand - supply gap. This gap is filled by load shedding, which results in public outcry, morchas, and loss of property. In every five year plans, GoI envisages generation capacity addition, but because of numerous reasons, the demand always outstrips the supply, and the utilities have to resort to load shedding. Capacity addition requires proper project management skills and has to overcome hurdles of land acquisition, rehabilitation, environmental problems, and so forth. In India, it is seen that generation projects are delayed by a significant amount of time. Demand side management (DSM) such as energy conservation programs can give an urgent relief to this problem, and will improve the electricity efficiency throughout the country. Electricity utility companies are executing various awareness campaigns for DSM (demand side management) . This paper tried to find out the reasons for demand supply gap in case of electricity, and examined the efforts of MSEDCL for the implementation of the energy saving campaign.